2020
DOI: 10.3390/ma13143226
|View full text |Cite
|
Sign up to set email alerts
|

Residual Strength Evaluation of Corroded Textile-Reinforced Concrete by the Deep Learning-Based Method

Abstract: Residual strength of corroded textile-reinforced concrete (TRC) is evaluated using the deep learning-based method, whose feasibility is demonstrated by experiment. Compared to the traditional method, the proposed method does not need to know the climatic conditions in which the TRC exists. Firstly, the information about the faster region-based convolutional neural networks (Faster R-CNN) is described briefly, and then procedures to prepare datasets are introduced. Twenty TRC specimens were fabricated and divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[4][5][6][7][8][9][10]. These subdisciplines provide a deeper grasp of learning and fundamental relationships, and allow for dealing with valuable datasets, diverse data sources, computer systems for data-concentrated functions, data privacy, and other related topics [11][12][13][14][15]. Nevertheless, ML is one of the most powerful and in-demand technologies globally [16][17][18][19][20].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…[4][5][6][7][8][9][10]. These subdisciplines provide a deeper grasp of learning and fundamental relationships, and allow for dealing with valuable datasets, diverse data sources, computer systems for data-concentrated functions, data privacy, and other related topics [11][12][13][14][15]. Nevertheless, ML is one of the most powerful and in-demand technologies globally [16][17][18][19][20].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Recently, with the development of industrial artificial intelligence along with computer technology, many studies have been reported using artificial intelligence to detect surface defects. The convolutional neural network (CNN) is an image-based deep learning algorithm and is a representative model used to surface inspection [ 4 , 5 , 6 , 7 , 8 , 9 ]. By repetitive training, features that define surface defects are automatically extracted without expert assistance.…”
Section: Introductionmentioning
confidence: 99%
“…TRC is a new type of cement-based composite material consisting of multidimensional fiber bundles and concrete matrix [ 5 , 6 ]. Compared to reinforcement steel, textile fiber has the advantages of high corrosion resistance [ 7 , 8 , 9 ] and light weight [ 10 ]. Moreover, TRC can effectively resist the effects of chloride ions and carbon dioxide in the environment due to the presence of high corrosion resistance of the fiber materials [ 11 ] (such as carbon fiber, alkali-resistant glass fiber, basalt fiber).…”
Section: Introductionmentioning
confidence: 99%